Docetism in the early church the quest for an elusive phenomenon - International colloquium "The quest for an elusive phenomenon: Docetism in the early church" 2014 Löwen; Verheyden, Joseph 1957-; Bieringer, Reimund 1957-; Schröter, Jens 1961-; Jäger, Ines; Menken, Maarten J. J. 1948-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2018)
Die Aufsätze in diesem Band befassen sich mit den Methoden, mit der die Forschung heutzutage versucht, Spuren von Doketismus in antiken Quellen, einschließlich der Evangelien und der Briefe des Johannes sowie zahlreicher Autoren des 2. Jahrhunderts, zu finden. Doketismus ist ein häufig verwendeter Ansatz in der Forschungsliteratur, um lose verbundene oder sogar äußerst unterschiedliche Phänomene oder Doktrinen zu bezeichnen, die alle mit der Definition des Wesens Christi und der Realität der Wiedergeburt und Passion Jesu zu tun haben. Das Symposium befasste sich aus einer neuen Perspektive mit dem Thema, indem es sich auf die antiken Dokumente selbst konzentrierte anstatt sich auf einer rein theoretischen oder dogmatischen Ebene zu bewegen und indem es den historischen Kontext, vor dem sie entstanden sind und verbreitet wurden, kritisch hinterfragte.InhaltsübersichtJoseph Verheyden: Introduction – Allen Brent: Can There be Degrees of Docetism? – Jörg Frey: »Docetic-like« Christologies and the Polymorphy of Christ: A Plea for Further Consideration of Diversity in the Discussion of »Docetism« – Francis Watson: Pauline Reception and the Problem of Docetism – Paul Foster: Christophany Stories in the Synoptic Gospels and Docetism – Jens Schröter: Eucharistie, Auferstehung und Vermittlung des ewigen Lebens: Beobachtungen zu Johannes und Ignatius (mit einem Ausblick auf Justin, Irenäus und das Philippusevangelium) – Reimund Bieringer: The Passion Narrative in the Gospel of John: A Hotbed of Docetism? – Maarten J.J. Menken: The Secessionists of the Johannine Epistles and Docetism – Alistair C. Stewart: Ignatius' »Docetists«: A Survey of Opinions and Some Modest Suggestions – Paul Anthony Hartog: The Impact of the Christological Controversies: Comparing the Ignatian Kerygma and Romans 1 – Dominika Kurek-Chomycz: »… the Flesh of Our Saviour Jesus Christ, Which suffered for Our Sins«: The Early Christian »Dying for« Formula, Suffering, and the Eucharist in IgnSm 7:1 – Taras Khomych: Conflicting Choreographies? Dance as Doctrinal Expression in Ignatius' Ephesians 19 and Acts of John 94–96 – Winrich Löhr: A Variety of Docetisms: Valentinus, Basilides and Their Disciples
This volume studies the ways modern research has tried to detect traces of Docetism in ancient sources, including the gospels and the Johannine epistles and several second-century authors. As a concept, Docetism is often used in scholarly literature for denoting loosely connected or even quite different phenomena or doctrines that all have to do with defining the nature of Christ and the reality of the incarnation and passion of Jesus. The essays presented here approach the topic from a new angle by focusing on the ancient documents themselves instead of staying on a purely theoretical or dogmatic level, while at the same time critically re-examining the historical contexts in which these were produced and first circulated. In some cases, this serves to once more reveal the hidden agendas that have guided modern scholars in their discussion of these topics.Survey of contentsJoseph Verheyden: Introduction – Allen Brent: Can There be Degrees of Docetism? – Jörg Frey: »Docetic-like« Christologies and the Polymorphy of Christ: A Plea for Further Consideration of Diversity in the Discussion of »Docetism« – Francis Watson: Pauline Reception and the Problem of Docetism – Paul Foster: Christophany Stories in the Synoptic Gospels and Docetism – Jens Schröter: Eucharistie, Auferstehung und Vermittlung des ewigen Lebens: Beobachtungen zu Johannes und Ignatius (mit einem Ausblick auf Justin, Irenäus und das Philippusevangelium) – Reimund Bieringer: The Passion Narrative in the Gospel of John: A Hotbed of Docetism? – Maarten J.J. Menken: The Secessionists of the Johannine Epistles and Docetism – Alistair C. Stewart: Ignatius' »Docetists«: A Survey of Opinions and Some Modest Suggestions – Paul Anthony Hartog: The Impact of the Christological Controversies: Comparing the Ignatian Kerygma and Romans 1 – Dominika Kurek-Chomycz: »… the Flesh of Our Saviour Jesus Christ, Which suffered for Our Sins«: The Early Christian »Dying for« Formula, Suffering, and the Eucharist in IgnSm 7:1 – Taras Khomych: Conflicting Choreographies? Dance as Doctrinal Expression in Ignatius' Ephesians 19 and Acts of John 94–96 – Winrich Löhr: A Variety of Docetisms: Valentinus, Basilides and Their Disciples
This volume is dedicated to the memory of our esteemed colleague Maarten J.J. Menken
"[...]selection of papers that were read at an international colloquium held at Leuven, December 3-5, 2014." - Introduction, Seite 1
Keywords: Wissenschaftliche Untersuchungen zum Neuen Testament; Christologie; Frühchristentum; Leid; Leib; Inkarnation; Aufsatzsammlung; Warten; Staatsrechtlehre; Privatisierung von Polizeiaufgaben; Universales Recht; Christology; Jesus; Eucharist; Neues Testament; Antike Religionsgeschichte; Kirchengeschichte; Array; Festschrift; Konferenzschrift -- 2014 -- Löwen